Meningkatkan partisipasi siswa melalui evaluasi interaktif dengan Kahoot pada kelas XB di MA Al-Hikam Jombang - Ayu, Diana Kusumaning (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the use of Kahoot as an interactive evaluation tool to increase the participation of class XB students at MA Al-Hikam Jombang. The research method used is qualitative with observation and interview techniques to obtain research data. The research subjects were students of class XB MA Al-Hikam Jombang. The research results show that using Kahoot significantly increases student participation from 50% to 85% after using Kahoot. Apart from that, using Kahoot can help increase students' motivation and enthusiasm in participating in learning.